2015
DOI: 10.1088/1742-6596/660/1/012059
|View full text |Cite
|
Sign up to set email alerts
|

A MEMS turbine prototype for respiration harvesting

Abstract: Abstract. The design, manufacturing, and performance characterization of a MEMS-scale turbine prototype is reported. The turbine is designed for integration into a respiration harvester that can convert normal human breathing into electrical power through electromagnetic induction. The device measures 10 mm in radius, and employs 12 blades located around the turbine periphery along with ball bearings around the center. Finite element simulations showed that an average torque of 3.07 μNm is induced at 12 lpm ai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…Few were the studies found in the systematic searches conducted in this review that harvested energy [ 77 , 84 , 104 ]. However, some energy harvesting techniques have been reported experimentally in other wearable systems [ 240 , 241 , 242 , 243 , 244 , 245 , 246 , 247 , 248 , 249 ]. This section presents a description of these techniques and how they were implemented in the respiratory sensing systems.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Few were the studies found in the systematic searches conducted in this review that harvested energy [ 77 , 84 , 104 ]. However, some energy harvesting techniques have been reported experimentally in other wearable systems [ 240 , 241 , 242 , 243 , 244 , 245 , 246 , 247 , 248 , 249 ]. This section presents a description of these techniques and how they were implemented in the respiratory sensing systems.…”
Section: Resultsmentioning
confidence: 99%
“…Other respiration-based energy harvesting systems can be found in the literature. The works of Delnavaz et al [ 240 ] and Goreke et al [ 241 ] used air flow to produce power with magnetic induction generators. On the one hand, the prototype of Delnavaz et al [ 240 ] was made up of two fixed magnets located at the ends of a tube (opposite poles facing each other) with a free magnet inside the tube ( Figure 13 B).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations